Optical Surface Scanning for Patient Positioning in Radiation Therapy: A Prospective Analysis of 1902 Fractions. (19th November 2018) - Carl, G; Reitz, D; Schönecker, S; Pazos, M; Freislederer, P; Reiner, M; Alongi, F; Niyazi, M; Ganswindt, U; Belka, C; Corradini, S
Purpose/Objective: Reproducible patient positioning remains one of the major challenges in modern radiation therapy. Recently, optical surface scanners have been introduced into clinical practice in addition to well-established positioning systems, such as room laser and skin marks. The aim of this prospective study was to evaluate setup errors of the optical surface scanner Catalyst HD (C-RAD AB) in different anatomic regions. Material/Methods: Between October 2016 and June 2017 a total of 1902 treatment sessions in 110 patients were evaluated. The workflow of this study included conventional setup procedures using laser-based positioning with skin marks and an additional registration of the 3-dimensional (3D) deviations detected by the Catalyst system. The deviations of the surface-based method were then compared to the corrections of cone beam computed tomography alignment which was considered as gold standard. A practical Catalyst setup error was calculated between the translational deviations of the surface scanner and the laser positioning. Two one-sided t tests for equivalence were used for statistical analysis. Results: Data analysis revealed total deviations of 0.09 mm ± 2.03 mm for the lateral axis, 0.07 mm ± 3.21 mm for the longitudinal axis, and 0.44 mm ± 3.08 mm vertical axis for the Catalyst system, compared to −0.06 ± 3.54 mm lateral, 0.53 ± 3.47 mm longitudinal, and 0.19 ± 3.49 mm vertical for the laser positioning compared to cone beam computed tomography. The lowest positional deviations were found in the cranial region, and larger deviations occurred in the thoracic and abdominal sites. A statistical comparison using 2 one-sided t tests showed a general concordance of the 2 methods ( P ≤ 0.036), excluding the vertical direction of the abdominal region ( P = 0.198). Conclusion: The optical surface scanner Catalyst HD is a reliable and feasible patient positioning system without any additional radiation exposure. From the head to the thoracic and abdominal region, a decrease in accuracy was observed within a comparable range for Catalyst and laser-assisted positioning.